Application of graphs in the analysis of vibrating 3-dimensional systems - Wojnarowski, Józef (Zielona Góra: Uniwersytet Zielonogórski)
Vibrating 3-dimensional mechanical systems are described by hybrid graphs. By dividing the hybrid graph into a tree and associated co-tree it is possible to describe in terms of matrices: across-flow-variables, stiffness and flexibility. The application of the formalism of graphs makes it possible to analyze mechanical systems in terms of dynamic characteristic and trajectory motion of determinate points.
Keywords: abstract graph; dynamic flexibility; transfer functions